Spiders on the case - Lasky, Kathryn; Gilpin, Stephen (New York : Scholastic Press, 2011)
Buster, a walnut orb weaving spider, enlists the help of Jo Beth, one of a family of poisonous but friendly brown recluse spiders, to help stop humans who are stealing from the rare books room of the Boston Public Library, where the spiders live.
School Library Journal, October 2011
4.5
K-3
Keywords: Brown recluse spider -- Juvenile fiction; Orb weavers -- Juvenile fiction; Spiders -- Juvenile fiction; Books and reading -- Juvenile fiction; Boston Public Library -- Juvenile fiction; Families -- Massachusetts -- Juvenile fiction; Boston (Mass.) -- Juvenile fiction; Brown recluse spider -- Fiction; Orb weavers -- Fiction; Spiders -- Fiction; Books and reading -- Fiction; Boston Public Library -- Fiction; Family life -- Massachusetts -- Fiction; Boston (Mass.) -- Fiction; Brown recluse spiders -- Fiction; Orb weavers -- Fiction; Spiders -- Fiction; Books and reading -- Fiction; Boston Public Library -- Fiction; Family life -- Massachusetts -- Fiction; Boston (Mass.) -- Fiction